(untitled) (Research, Society and Development, 2023)
Objective: To describe the strategies for preventing cervical cancer in Primary Health Care (PHC). Method: This is an integrative literature review, carried out in October and November 2022, in the MEDLINE, LILACS and BDENF databases, by crossing the descriptors: “Health Strategies”, “Pap Smear Test”, “Primary Health Care” and “Uterine Cervical Neoplasms”, through the Boolean operators “AND” and “OR”, as an inclusion criterion, articles that addressed the theme, r related to Portuguese, English and Spanish, and publications available in full and free of charge. And as exclusion criteria, studies that did not address the theme, in addition to repeated publications. For the final sample, 09 studies were left. Results and Discussions: In the PHC there are services that prevent and reduce cases of cervical cancer, with this, recruitment, active search and education for self-care are used as strategies to increase adherence, thus investing in the qualification of the health system to reduce morbidity and mortality rates due to this condition, through effective and efficient preventive and health promotion actions. Final considerations: In view of this, it is possible to conclude that PHC strategies are adopted to prevent cervical cancer. However, it is necessary to expand the meaning of care for women, seeking to redefine self-care, through participatory and dialogic approaches, and strategies that are able to revert to the reality of persistent rates of this type of gynecological cancer.